2006
DOI: 10.1097/01.tp.0000208573.16839.67
|View full text |Cite
|
Sign up to set email alerts
|

Perforin, Granzyme B, and Fas Ligand for Molecular Diagnosis of Acute Renal-Allograft Rejection: Analyses on Serial Biopsies Suggest Methodological Issues

Abstract: Two lytic pathways are activated in biopsies when AR occurs shortly after Tx, whereas the P/GB mechanism prevails if it occurs later on. Only P and FL in biopsies might be able to predict AR diagnosis, but with a considerable variability in each sample, possibly due to the small portion of tissue core, which may be inadequate for molecular diagnosis. CTL expression in PBL does not correlate with histological AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 36 publications
0
19
1
1
Order By: Relevance
“…These results are in accordance with studies conducted by a number of groups including Netto et al [10], Sabek et al [19], Simon et al [9], Shin et al [24], and Vasconcellos et al [25], which showed increased perforin and/or granzyme-B levels in the peripheral blood of renal allograft recipients undergoing acute rejection. Recent data by Graziotto et al, however, reported that perforin and granzyme-B expression levels in the peripheral blood did not correlate with histologic acute rejection [26]. This inconsistency from our results may be related to differences in allosensitization among the study populations.…”
Section: Discussioncontrasting
confidence: 75%
“…These results are in accordance with studies conducted by a number of groups including Netto et al [10], Sabek et al [19], Simon et al [9], Shin et al [24], and Vasconcellos et al [25], which showed increased perforin and/or granzyme-B levels in the peripheral blood of renal allograft recipients undergoing acute rejection. Recent data by Graziotto et al, however, reported that perforin and granzyme-B expression levels in the peripheral blood did not correlate with histologic acute rejection [26]. This inconsistency from our results may be related to differences in allosensitization among the study populations.…”
Section: Discussioncontrasting
confidence: 75%
“…Cytokines and the molecules associated with cytolytic effector functions of T lymphocytes have long been studied as surrogates of AR and as possible candidates to the development of a non-invasive diagnostic tool [18][19][20][21][22][23]. Although with some good initial results, none of the proposed markers studied, until now, are being used routinely in the clinical practice or gained full acceptance.…”
Section: Discussionmentioning
confidence: 95%
“…Studies regarding messenger RNA profiles using real-time polymerase chain reaction have reported that expression of Granzyme B and perforin in the peripheral blood, which are the cytotoxic T-cell markers, was up-regulated during acute rejection in KTRs (171819202122). However, a recent meta-analysis regarding the significance of Granzyme B and perforin as noninvasive diagnostic biomarkers for acute rejection have demonstrated that neither Granzyme B nor perforin alone could be a reliable noninvasive diagnostic biomarker for acute rejection in KTRs (23).…”
Section: Discussionmentioning
confidence: 99%